2021
DOI: 10.1590/0037-8682-0590-2020
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of triatomines (Hemiptera, Reduviidae) and their natural infection by Trypanosoma cruzi (Chagas, 1909) in Boca do Moa community, Cruzeiro do Sul, Acre, Brazil

Abstract: INTRODUCTION: Triatomines are insect vectors of Trypanosoma cruzi , the etiological agent of Chagas disease. METHODS: Triatomines were collected from households and by dissecting palm trees in the peri-urban areas of Cruzeiro do Sul (Acre); they were identified using a specific key and via genital analyses. Trypanosomatid infection was determined through microscopy and polymerase chain reaction. RESULTS: In total, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Nova Cintra is a relatively understudied area situated in one of the main parasite circulation zones. The presence of T. cruzi -positive triatomine bugs was confirmed in both communities, along with positive cases of Chagas disease in Nova Cintra in 2016 (Muniz, 2016; Madeira et al, 2020; Jesus et al, 2021) [ 11 , 12 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nova Cintra is a relatively understudied area situated in one of the main parasite circulation zones. The presence of T. cruzi -positive triatomine bugs was confirmed in both communities, along with positive cases of Chagas disease in Nova Cintra in 2016 (Muniz, 2016; Madeira et al, 2020; Jesus et al, 2021) [ 11 , 12 , 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have confirmed the presence of T. cruzi -positive triatomine bugs in remote riverine communities, away from major urban centers. This finding is significant for conducting research involving populations residing in these areas, as it increases the potential for these communities to become outbreak settings for Chagas disease (Madeira et al, 2020; Jesus et al, 2021; Souza et al, 2021) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caused by Trypanosoma cruzi, a protozoan normally transmitted by the bite of Triatoma infestans (blood-sucking beetles) which, after being bitten, defecates releasing T. cruzi, which penetrates through injured regions or in contact with the mucous membranes, and starts the cycle in mammals. Endemic to Latin America, Chagas disease can be transmitted orally by eating food contaminated by parasite (De Jesus et al, 2021;De Morais et al, 2015;Dias et al, 2014;Herrera et al, 2015;Martins-Melo et al, 2019;Pérez-Molina et al, 2015;Shender et al, 2016). In addition, this disease has been a concern in developed countries that have identified immigrants who presented the parasite and cause dissemination via blood and placental transmission (Antinori et al, 2017;Garcia et al, 2015), with an estimated 75 million people at risk of infection, especially in the 21 countries of Latin America (Aguilar et al, 1999;Costa et al, 2021;Garcia et al, 2015;Santana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there may be an erroneous description of the distribution of R. montenegrensis, both in Brazil and in other Latin American countries (with an emphasis on countries bordering Brazil). R. montenegrensis specimens collected from palm trees and residences revealed their ability to adapt to the human environment, dispersal, and mobility 17 . Studies conducted in Acre, Amazonas, and Rondônia demonstrate the predominance of this species in its natural ecotope, and intrusion into residences and the infection rate for T. cruzi in this species are significant in the localities where they were captured [9][10][11]17 .…”
mentioning
confidence: 99%
“…R. montenegrensis specimens collected from palm trees and residences revealed their ability to adapt to the human environment, dispersal, and mobility 17 . Studies conducted in Acre, Amazonas, and Rondônia demonstrate the predominance of this species in its natural ecotope, and intrusion into residences and the infection rate for T. cruzi in this species are significant in the localities where they were captured [9][10][11]17 . Another aspect described in these studies is the non-occurrence of domiciliation of R. montenegrensis 10,17 .…”
mentioning
confidence: 99%